ASSISTANCE IN IMPROVING QUALITY OF EDUCATION IN EARLY CHILDREN BASED ON STANDARD PAUD IN DELI SERDANG DISTRICT - Marbun, Sariana (Journal of Community Research and Service, 2019)
Activities in Quality Improvement of ECD Management Based on ECD Standards based on the low understanding of managers (principals and teachers) on eight PAUD Standards (Standards for Achieving Child Development, Content, Processes, Educators and Education Personnel, Assessment, Facilities and Infrastructure, Management and Financing). This activity aims to assist principals and teachers in managing PAUD based on PAUD standards. The activities carried out began with enlightenment and question and answer about the Nature of PAUD Standards, then analyzed the Instruments for PAUD Quality Mapping, and Assistance in completing the documents of each Standard. Mentoring activities were carried out from August to October 2018, which took place at PAUD Miska and PAUD Harapan Bangsa, Percut Sei Tuan District, Deli Serdang Regency. The participants of this activity were the Principal and Teachers and Education Personnel who served in the two schools totaling 10 people. Activities are carried out by means of discussion, question and answer, group work and assignments. At the end of the activity an evaluation of the process and work results of the participants was conducted, and agreed on follow-up activities from mentoring. The results of the mentoring activities concluded that: 1) Understanding of Principals and teachers and other education personnel about PAUD management Based on PAUD Standards increased; 2) Managers' lack of understanding of PAUD Standards causes a lack of realization of programs that refer to standards, lack of procurement of facilities and infrastructure, and not storing documents or letter files, certificates, photos, attendance lists and others. It is recommended that PAUD managers try to rediscover some of the physical evidence that the activities that have been carried out are in accordance with the standards, and the following day the manager must carry out the program in accordance with the PAUD Standards.Keywords: Assistance in Quality Improvement of PAUD Management, PAUD Standards.